2018
DOI: 10.1016/j.jamcollsurg.2018.04.032
|View full text |Cite
|
Sign up to set email alerts
|

Opioid Medication Use in the Surgical Patient: An Assessment of Prescribing Patterns and Use

Abstract: Postoperative patients might consume less than half of the opioid pills they are prescribed. More research is needed to standardize opioid prescriptions for postoperative pain management while reducing opioid diversion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
43
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(46 citation statements)
references
References 29 publications
(24 reference statements)
2
43
0
1
Order By: Relevance
“…Conversely, every patient had leftover opioid pills at the end of the study. These results are consistent with a recent report by Tan et al, which showed that postoperative patients following open and laparoscopic abdominal surgical procedures required fewer than half of the opioid pills prescribed. Although there are obvious differences in pre‐ and postoperative characteristics between patients undergoing abdominal and rhinologic surgery, the phenomenon of opioid overprescribing appears to span many surgical disciplines.…”
Section: Discussionsupporting
confidence: 93%
“…Conversely, every patient had leftover opioid pills at the end of the study. These results are consistent with a recent report by Tan et al, which showed that postoperative patients following open and laparoscopic abdominal surgical procedures required fewer than half of the opioid pills prescribed. Although there are obvious differences in pre‐ and postoperative characteristics between patients undergoing abdominal and rhinologic surgery, the phenomenon of opioid overprescribing appears to span many surgical disciplines.…”
Section: Discussionsupporting
confidence: 93%
“…The primary outcome was total opioid dose per index prescription in morphine milligram equivalent (MME), a measure that reflects both the dose and number of tablets in the entire prescription and standardizes across opioid type. 24 Although the outcome MME/day is commonly used in the literature, MME/prescription has been used previously in opioid prescribing policy 25,26 and hospital and health system-based studies 27,28 and allowed us to report change in the total volume of opioids in a new prescription. Further, by using total MME/prescription, we were able to distinguish between true decreases in prescribing and changes in dosing instructions (i.e., increasing the dose or frequency to fit within 5 days).…”
Section: Discussionmentioning
confidence: 99%
“…4,[6][7][8] Studies have shown there is a large MED range of opiate medications provided to patients after common surgeries, 9 and that a majority of patients report unused leftover opioid medication after procedures. 7,8,10 Specifically, unanticipated visits after ureteroscopy for stone disease has been reported to be 6.6%, and the majority of these visits are made due to pain. 5,11 An important finding of our study is that most patients before stone surgery have had opiate exposure within the previous 30 days, and a significant proportion have had multiple prescriptions.…”
Section: Discussionmentioning
confidence: 99%
“…After surgery, providing a standardized MED per postoperative opiate prescription may help minimize the quantity of opiates prescribed and/or unused by patients. 10 It is important to note that patients who have had prior exposure to opiate medications seem to be at greater risk for continued opiate use, and these at-risk patients may benefit most from targeted counseling regarding the risks and alternatives to opiate medications. Furthermore, providing prescriptions for nonopiate medications including nonsteroidal anti-inflammatory drugs, alpha-blockers, oxybutynin, and phenazopyridine may result in decreased opiate requirement.…”
Section: Discussionmentioning
confidence: 99%